Using new forms of information and communication technologies to empower SMEs - Jia S.; Tseng H.-T.; Shanmugam M.; Rees D.J.; Thomas R.; Hajli N. (Emerald Publishing, 2023)
article; communication technology; electronic commerce; entrepreneurship; food; human; partial least squares regression; structural equation modeling; trust